?Analytical Studies on Biologically Active Compounds. Part II. Separation and quantitation of mixtures of isatin derivatives for application to metabolism studies: ?Short Communication (Biological Sciences - PJSIR, 1995)
Seven different mixtures of three, four and five com- pounds randomly selected were prepared for qualitative analy- sis. The same mixtures were prepared using accurately mea- sured amounts for separation and quantitative determination of individual components.